INFLUNCE OF AUXIN AND POLYAMINEES ON ROOTING OF SHOOTS OF CITRUS VOLKAMERIANA ROOTSTOCK IN VITRO - & Hamad, Al- Khazali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This research was conducted in the plant tissue culture Lab. College of Agriculture / University of Baghdad from February to October 2015. The aim of the study was investigating the influence of combinations of Indole butyric acid (IBA) , Naphthalene acetic acid (NAA) and polyamine Spermidine (Spd.) on rooting of shoots of citrus volkameriana rootstock cultured on 1\2 MS medium. The Results indicated that 1/2 MS medium supplemented with 1.0 mg L-1 (IBA) gave the highest percentage of rooting (67 %) which differed significantly from the MS medium with free auxin IBA that gave (22%) while the MS medium supplemented with 0.5 mg L-1 spermidine gave the highest percentage of rooting (63%) that was not significantly different than other concentrations of Spd . MS medium supplemented with 1.0 mg L-1 IBA and 0.5 mg L-1 Spd. gave the highest percentage of rooting (83%) and the highest root number / shoot (3.17) and highest length of root (3.15 cm) while the MS medium with free auxin IBA and spd. did not give percentage of rooting (0%) for citrus volkameriana rootstock plantlets . The MS medium supplemented with 1.0 mg L-1 NAA gave the highest percentage of rooting (56%) which differed significantly from MS medium with free auxin NAA that gave (22%) while MS medium supplemented with 0.5mg L-1 spd. gave the highest percentage of rooting (50%) that was not significantly different from other concentration of Spd . MS medium supplemented with 1.0 mg L-1 NAA and 0.5 mg L-1 Spd. gave the highest percentage of rooting (68%) and the highest root number /shoot (2.5) and highest length of root (2.65 cm) while the MS medium with free auxin NAA and Spd. did not gave percentage of rooting (0%) .